2018
DOI: 10.1186/s12877-018-0813-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between vascular comorbidity and progression of Alzheimer’s disease: a two-year observational study in Norwegian memory clinics

Abstract: BackgroundVascular risk factors increase the risk of Alzheimer’s disease (AD), but there is limited evidence on whether comorbid vascular conditions and risk factors have an impact on disease progression. The aim of this study was to examine the association between vascular disease and vascular risk factors and progression of AD.MethodsIn a longitudinal observational study in three Norwegian memory clinics, 282 AD patients (mean age 73.3 years, 54% female) were followed for mean 24 (16–37) months. Vascular ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…This means that of those patients who developed dementia, 77.2% had obtained a result below the cut-off point, compared to 41.4% in those who did not develop the disease, which is very similar to our results (see Table 5). In addition, they observed that the dif- This result is in line with other studies which did not find this association either in MCI patients [20] [38].…”
Section: Discussionsupporting
confidence: 87%
“…This means that of those patients who developed dementia, 77.2% had obtained a result below the cut-off point, compared to 41.4% in those who did not develop the disease, which is very similar to our results (see Table 5). In addition, they observed that the dif- This result is in line with other studies which did not find this association either in MCI patients [20] [38].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the group of AD patients not classified with CVD may also have had some CVD, as many of them had some degree of WMH on MRI (Fazekas score of 1) and most had vascular risk factors (35).…”
Section: Discussionmentioning
confidence: 72%
“…Cardiovascular disorders are very common in patients with AD. Up to 83% of these patients have arterial hypertension and 16% have ischemic heart disease, whereas 15% of them have suffered a cerebrovascular event [ 39 ]. Another study found a prevalence of 55.1% for arterial hypertension and 22.7% for cerebrovascular disease [ 40 ].…”
Section: Dysautonomia As a Results Of Comorbidities And Medicationmentioning
confidence: 99%
“…Another major comorbidity in the elderly is diabetes mellitus, with a prevalence of 9–25.7% [ 39 , 40 ]. Diabetes mellitus is regarded as a common cause of neuropathy-associated autonomic dysfunction.…”
Section: Dysautonomia As a Results Of Comorbidities And Medicationmentioning
confidence: 99%